Cross talk between intracellular pathogens and cell death. Issue 1 (22nd June 2020) - Demarco, Benjamin; Chen, Kaiwen W.; Broz, Petr
Abstract: Infections with bacterial pathogens often results in the initiation of programmed cell death as part of the host innate immune defense, or as a bacterial virulence strategy. Induction of host cell death is controlled by an elaborate network of innate immune and cell death signaling pathways and manifests in different morphologically and functionally distinct forms of death, such as apoptosis, necroptosis, NETosis and pyroptosis. The mechanism by which host cell death restricts bacterial replication is highly cell‐type and context depended, but its physiological importance is highlighted the diversity of strategies bacterial pathogens use to avoid induction of cell death or to block cell death signaling pathways. In this review, we discuss the latest insights into how bacterial pathogens elicit and manipulate cell death signaling, how different forms of cell death kill or restrict bacteria and how cell death and innate immune pathway cross talk to guard against pathogen‐induced inhibition of host cell death.